1998
DOI: 10.1073/pnas.95.21.12424
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis regulator Bcl-w is essential for spermatogenesis but appears otherwise redundant

Abstract: Proteins of the Bcl-2 family are important regulators of apoptosis in many tissues of the embryo and adult. The recently isolated bcl-w gene encodes a pro-survival member of the Bcl-2 family, which is widely expressed. To explore its physiological role, we have inactivated the bcl-w gene in the mouse by homologous recombination. Mice that lack Bcl-w were viable, healthy, and normal in appearance. Most tissues exhibited typical histology, and hematopoiesis was unaffected, presumably due to redundant function wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
204
2
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(223 citation statements)
references
References 43 publications
(51 reference statements)
10
204
2
7
Order By: Relevance
“…7,8,13,14 On the other hand, the mice with systemic deletion of the mcl-1 or bcl-x gene died in the embryo stage due to implantation failure or erythrocyte and neuronal apoptosis, respectively, 6,29 which did not provide information about their involvement in the survival of the megakaryocytic lineage. However, Pf4-Cre transgenic mice have recently been developed, and any target gene can be deleted exclusively from their megakaryocytes and platelets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,13,14 On the other hand, the mice with systemic deletion of the mcl-1 or bcl-x gene died in the embryo stage due to implantation failure or erythrocyte and neuronal apoptosis, respectively, 6,29 which did not provide information about their involvement in the survival of the megakaryocytic lineage. However, Pf4-Cre transgenic mice have recently been developed, and any target gene can be deleted exclusively from their megakaryocytes and platelets.…”
Section: Discussionmentioning
confidence: 99%
“…12 Genetic studies deleting other anti-apoptotic Bcl-2 family genes have not reported any abnormality of the megakaryocytic lineage. 7,8,13,14 Therefore, the essential anti-apoptotic actors regulating survival of the megakaryocytic lineage, especially megakaryocytes, have been unclear and disputed.…”
mentioning
confidence: 99%
“…This single finding is consistent with inhibition of cell cycle reentry or G1 to S transition by BCL-w overexpression, but the physiological significance of this was not substantiated in bcl-w À/À mice. 36 MCL-1 was originally identified as an upregulated gene in a human myeloblastic leukemia cell line induced to differentiate in the monocyte lineage. 37 Overexpression of this gene in cell lines caused decreased BrdU uptake and slower doubling rate.…”
Section: Other Antiapoptotic Bcl2 Family Membersmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Bcl-W −/− mice have impaired spermatogenesis. 16,17 A1 remains the only pro-survival BCL-2 family member for which a knockout mouse strain has not been developed. A1 was first discovered as a GM-CSF-inducible gene with significant sequence similarity to BCL-2 and MCL-1, 18 and its human homologue BFL-1 was later identified in fetal liver.…”
mentioning
confidence: 99%